(untitled) (Acta Polytechnica CTU Proceedings, 2017)
During experiments on vehicle simulators a large amount of data is stored. On these data, it is possible to trace some similarities in the behavior of drivers in certain areas or when performing the same task. We can assume that if the driver performs a certain type of experiment, his behavior exhibits certain traits. These elements of common behavior can be used to create virtual track for experiments. Which elements and how they can be used is described in this article. The algorithm for automatic creation of virtual track based on type of experiment is provided. It will help us to define the purpose of measurement and the track could be generated automatically.